Analysis of the Influence of the Marketing Mix (7P) on Inpatient Satisfaction at Siaga Al-Munawwarah Hospital, Samarinda - Ahmad Yusron; Nur Rohmah; Riyan Ningsih (Pascasarjana, Mataram University, 2026)
The role of the marketing mix today is not only to provide products or services to consumers but also how these products or services provide satisfaction to consumers or customers so that they will attract consumer interest to continue purchasing the products or services offered. The purpose of this study is to determine the influence of the 7P marketing mix on the satisfaction of inpatients at the Siaga Al-Munawwarah Hospital in Samarinda. This research is a quantitative cross-sectional design. This study used a sectional approach, with a sample of 274 respondents. The study period was January - September 2025, of inpatient at the Siaga Al-Munawwarah Hospital in Samarinda. The analysis used univariate, bivariate, and multivariate methods. The statistical tests used were the chi-square test and logistic regression. The results of the study showed that there was an influence of place (p-value 0.005), process (p-value 0.010) on inpatient satisfaction. Based on the logistic regression test, it was found that place is the variable that has the most influence on the satisfaction of inpatients. This study shows that there is a significant influence of the place and process variable on inpatient satisfaction